Assessment of Anxiety and Depression among Patients with Substance Use Disorder Attending at a selected Rehabilitation Center Kathmandu, Nepal - Kalpana Regmi; Rita Kumari Ban; Ambika Baniya (Journal of Karnali Academy of Health Sciences, 2021)
Background: Anxiety and depression are two important contributors to the global burden of disease. Both conditions are frequently found as comorbidity among patients with substance use disorder and play a major role in its prognosis and relapse. If ignored such psychiatric illness by a mental health professional, can create a gap in the overall treatment outcome of substance use disorder.